Proceedings of the IEEE 1996 Virtual Reality Annual International Symposium 1996
DOI: 10.1109/vrais.1996.490521
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality system effects on size-distance judgements in a virtual environment

Abstract: The following paper provides an assessment of how selected properties of a virtual reality system impact size-distance judgments in a virtual environment. Manipulations are made in viewing conditions (biocular vs. stereoscopic), image resolution, field of view, scene contrast, and target distance, while subjects attempt to match the attributes of a comparison object with a standard object. General findings suggest that under more natural viewing conditions, size-distance judgments in virtual environments diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…Perceptual matching tasks were also applied. Some authors asked their participants to match the distance or the size of a target object as compared to a reference object, respectively [e.g., Eggleston et al 1996;Kenyon et al 2007b;Li et al 2011;Sinai et al 1999]. Others instructed them to indicate the midpoint of a distance [e.g., Bodenheimer et al 2007] or to indicate which of two objects was closer [e.g., Bruder et al 2012;Surdick and Davis 1997].…”
Section: The Variety Of Measurement Methodsmentioning
confidence: 99%
“…Perceptual matching tasks were also applied. Some authors asked their participants to match the distance or the size of a target object as compared to a reference object, respectively [e.g., Eggleston et al 1996;Kenyon et al 2007b;Li et al 2011;Sinai et al 1999]. Others instructed them to indicate the midpoint of a distance [e.g., Bodenheimer et al 2007] or to indicate which of two objects was closer [e.g., Bruder et al 2012;Surdick and Davis 1997].…”
Section: The Variety Of Measurement Methodsmentioning
confidence: 99%
“…1,6 This effect may be attributed to a variety of factors including hardware errors, software errors, and perception errors. Recently, Kenyon et al 12 have shown size-constancy in a VE (CAVE) and that monocular cues to depth play a major role in sizeconstancy performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that spatial perception is affected by several parameters, and this is also likely to affect exocentric judgement. Significant parameters for the perception of spatial perception are navigational interface (Witmer and Kline 1998), display type (Eggleston, Janson, and Aldrich 1996;Henry and Furness 1993;Yeh and Silverstein 1992), quality of the computer graphics (Thompson et al 2002) and scene contrast (Eggleston, Janson, and Aldrich 1996). The effect of shadow sharpness and shadow shape on the relation of spatial size, position and shape has been investigated by Wanger (1992).…”
Section: Implications With Virtual Assessmentsmentioning
confidence: 99%